Sediment disasters caused by the 2016 Kumamoto Earthquake and regional disaster history - M. Suzuki; K. x Kagohara; K. Sakaguchi; H. Matsugi; S. Kataoka (International Association of Lowland Technology, 2017)
In the 2016 Kumamoto earthquake, a lot of landslides, slope failures and debris flows occurred in mountainous regions around Mt. Aso. Most of the failed slopes were located near the earthquake faults caused strong vibrations. Although there was very little rainfall before the earthquakes, debris flows occurred along the mountain streams and eventually travelled long distances. It is noted that volcanic soil, being fragile and sensitive to disturbances, was widely distributed within the affected area. In this research, the conditions of large-scale failure, landslide, and debris flow are investigated to clarify the characteristics and history of earthquake-induced sediment disasters in the volcanic regions based on the results obtained from our investigation.